Modern Challenges in Rational Pharmacotherapy Design: The Multifaceted Role of Color in the Development and Application of Solid Dosage Forms - Kurylo , Zoryana; Panysheva, Oksana (The Ukrainian Scientific Medical Youth Journal, 2026)
Introduction. In the paradigm of rational pharmacotherapy, the visual attributes of solid dosage forms (SDFs), particularly their color, emerge as a complex factor influencing both physicochemical stability and treatment safety. Aim. The aim of this research was to systematize scientific data on the role of SDF color in ensuring photostability, accurate identification, excipient safety, and improving medication adherence. Materials and Methods. Based on the PRISMA methodology, a systematic analysis of scientific literature for the period 2024–2026 was conducted using PubMed, Scopus, Web of Science, and Google Scholar databases, covering the screening of 989 publications and a critical review of 35 source materials. Results. It was established that the directional hemispherical reflectance (DHR) parameters of the SDF coating determine its photoprotective attributes, preventing active substance degradation. Color differentiation of doses serves as an effective tool to minimize Look-Alike, Sound-Alike (LASA) errors, thereby enhancing patient safety in cases of polypharmacy. The current regulatory status of titanium dioxide (TiO₂, E171) was evaluated according to EMA and EFSA documents, alongside the technological prospects of implementing natural plant and microbial pigments. The impact of color semantic resonance on shaping patient expectations and modulating placebo/nocebo effects was reviewed. Conclusions. Therefore, a justified choice of color palette at the preformulation stage is an essential element of patient-centric design of SDFs to optimize storage conditions and support proper medication adherence.